Interaction interface in the C-terminal parts of centriole proteins Sas6 and Ana2. Issue 11 (11th November 2020) - Fatalska, Agnieszka; Dzhindzhev, Nikola S.; Dadlez, Michal; Glover, David M.
Abstract : Abstract : The centriole is a ninefold symmetrical structure found at the core of centrosomes and, as a basal body, at the base of cilia, whose conserved duplication is regulated by Plk4 kinase. Plk4 phosphorylates a single serine residue at the N-terminus of Ana2 to promote Ana2's loading to the site of procentriole formation. Four conserved serines in Ana2's STAN motif are then phosphorylated by Plk4, enabling Sas6 recruitment. Crystallographic data indicate that the coiled–coil domain of Ana2 forms a tetramer but the structure of full-length Ana2 has not been solved. Here, we have employed hydrogen–deuterium exchange coupled with mass spectrometry (HDX-MS) to uncover the conformational dynamics of Ana2, revealing the high flexibility of this protein with one rigid region. To determine the elusive nature of the interaction surfaces between Ana2 and Sas6, we have confirmed complex formation between the phosphomimetic form of Ana2 (Ana2-4D) and Sas6 in vitro and in vivo . Analysis of this complex by HDX-MS identifies short critical regions required for this interaction, which lie in the C-terminal parts of both proteins. Mutational studies confirmed the relevance of these regions for the Ana2–Sas6 interaction. The Sas6 site required for Ana2 binding is distinct from the site required for Sas6 to bind Gorab and Sas6 is able to bind both these protein partners simultaneously.